(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Five organic amendments were evaluated against wilt of lentil which were found more or less effective. Maximum disease control (42.85%) found in neem cake followed by mustard cake (38.23%), parthenium (32.90%), linseed cake (28.57%) and sawdust was least in reducing wilt (23.66%) in 2016- 17. Similar results were also observed in the year 2017-18.Inhibitory effect of bioagents was tested against Fusarium oxysporum f. sp. lentis in vitro. Maximum(65.94%) mycelial growth was inhibited by Pseudomonas fluorescens followed by Bacillus subtilis (62.23%), T. viride (39.62%)and T. virense (39.22%).T. harzianum was found least effective inhibition of mycelia growth (35.65%) in dual plate technique. All five bio-agents evaluated against F. o. f. sp. lentis in vitro were also tested in vivo conditions, where they also were found effective in wilt management. Maximum disease control (42.10%) was recorded with P. fluorescens@ 10 g/kg seed followed by Bacillus subtilis (38.27%) @ 10 g/kg seed, T. viride (32.70%) @ 4 g/kg seed and T. virens (32.80%) @ 4 g/kg seed . T. harzianum was least effective in reducing wilt incidence (30.40%) @ 4 g/kg seed in 2016-17. Similar results were also observed in the year 2017-18. Disease incidence was maximum at 90 days after sowing as compared to 60 and 30 days after sowing in both the years.